Impact of an active educational video game on children's motivation, science knowledge, and physical activity - Haichun Sun; Yong Gao (Elsevier, 2016)
Background: Active educational video games (AVGs) appear to have a positive effect on elementary school students' motivation leading to enhanced learning outcomes. The purpose of this study was to identify the effectiveness of an AVG on elementary school students' science knowledge learning, physical activity (PA) level, and interest-based motivation. Methods: In this randomized controlled study, 53 elementary school students were assigned to an experimental condition or a comparison condition. The experimental condition provided an AVG learning environment, whereas the comparison condition was based on sedentary educational video games. Results: The results of repeated measures analysis of variance (ANOVA) on the knowledge test showed that students in both groups performed better on the post-test than they did on the pre-test (p < 0.001, η2 = 0.486), and their post-test scores did not differ significantly. The experimental condition provided a more active environment since the students' average heart rates (HRs) were in the Target-Heart-Rate-Zone (HR = 134 bpm), which was significantly higher than the average HR (103 bpm) from the comparison condition (t = 7.212, p < 0.001). Students in the experimental condition perceived a higher level of situational interest than their counterparts in the comparison group (p < 0.01, and η2 = 0.301). Conclusion: These results suggest that AVGs benefit children more in terms of PA and motivation than traditional video games by providing an enjoyable learning experience and sufficient PA.